"Gizi COVID-19 Bagi Remaja" Application as A COVID-19 Prevention - Rahayu, Sri Ratna; Sulistiani, Duwi; Yuniastuti, Ari; Merzistya, Aufiena Nur Ayu (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Adolescents are a vulnerable group in fulfilling nutrition for body defence as an effort to prevent COVID-19. Nutrition education is needed for adolescents to increase their knowledge of nutrition consumption. One of the models to improve nutrition knowledge used the Android-based smartphone nutrition application model. This research aimed to design and develop a nutrition android application model to increase adolescents' nutritional knowledge in the prevention of COVID-19. The method used Research & Development with four stages: the analysis stage, the design stage, the development stage, and the testing stage. This research produced the "Gizi COVID-19 Bagi Remaja" as a nutrition application android-based with 3 main menus, namely BMI and calories checking, nutrition info, and COVID-19 info.Ã‚Â  The N-Grain test results show that this application effectively increases nutritional knowledge in 10 high school-adolescents (N-Grain=88.21%). The Android-based Ã¢â‚¬Å“Gizi COVID-19 RemajaÃ¢â‚¬Â application is expected to be a comprehensive media for adolescents nutrition education during the COVID-19 pandemic in Indonesia to prevent the transmission of COVID-19.